2022
DOI: 10.1186/s11658-022-00323-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying pathways regulating the oncogenic p53 family member ΔNp63 provides therapeutic avenues for squamous cell carcinoma

Abstract: Background ΔNp63 overexpression is a common event in squamous cell carcinoma (SCC) that contributes to tumorigenesis, making ΔNp63 a potential target for therapy. Methods We created inducible TP63-shRNA cells to study the effects of p63-depletion in SCC cell lines and non-malignant HaCaT keratinocytes. DNA damaging agents, growth factors, signaling pathway inhibitors, histone deacetylase inhibitors, and metabolism-modifying drugs were also investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…In conclusion, we have shown that inhibiting DNA methylation causes a switch in the relative levels of p63 isoforms, potentially converting ΔNp63-mediated tumor promotion and therapy resistance ( 7 9 , 12 , 13 ) towards TAp63-mediated tumor suppression ( 3 , 4 , 6 , 10 , 11 ). By identifying DNA hypermethylation at the TAP63 promoter in SCC, these data add this gene to the list of tumor suppressors that are epigenetically silenced in malignancy ( 40 42 ).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In conclusion, we have shown that inhibiting DNA methylation causes a switch in the relative levels of p63 isoforms, potentially converting ΔNp63-mediated tumor promotion and therapy resistance ( 7 9 , 12 , 13 ) towards TAp63-mediated tumor suppression ( 3 , 4 , 6 , 10 , 11 ). By identifying DNA hypermethylation at the TAP63 promoter in SCC, these data add this gene to the list of tumor suppressors that are epigenetically silenced in malignancy ( 40 42 ).…”
Section: Discussionmentioning
confidence: 79%
“…Plasmid DNAs were isolated using a Plasmid Maxi Kit (12162, Qiagen, Hilden, Germany) and used to produce viral particles in HEK293FT cells (ATCC). Lentiviruses were collected 48 and 96 h after transfection and transduced into HaCaT, FaDu and SCC-25 cells as described previously ( 12 ). Medium was replaced after 24 h, and selection in puromycin (1 µg/ml for HaCaT and FaDu and 0.05 µg/ml for SCC-25) started after a further 24 h. Medium containing puromycin was replaced every three days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metformin (1, 1-dimethyl biguanide) is a cost-effective and safe medication that helps diabetic patients to reduce their blood sugar levels. It has exhibited anti-tumorigenic effects in both experimental and clinical studies, suggesting a promising potential role in the treatment of multiple cancer treatments, such as ovarian cancer, lung adenocarcinoma, and breast cancer [ 87 90 ]. Metformin has been widely used by diabetic patients for over 40 years, but more recently a growing body of evidence suggests that metformin may also modulate the phenotype and the number of non-transformed cell types in the TME, such as CAFs, endothelial cells, and innate and adaptive immunity cells, including TAMs and T-lymphocytes, by multiple strategies [ 91 ].…”
Section: Metformin and Cancer Therapymentioning
confidence: 99%